CHEMICAL CONTROL OF PHYTOPHTHORA WILT IN TOMATOES - Prazeres Mendonca, Lais Barbosa; Coelho, Lisias; Stracieri, Juliana [UNESP]; Ferreira Junior, Joao Batista [UNESP]; Tebaldi, Nilvanira Donizete (Univ Federal Uberlandia, 2015)
The most effective disease management method for yield reducing diseases affecting tomatoes is the use of fungicides. This study evaluated the efficacy of chemical control on three Phytophthora sp. isolates, pathogenic to tomatoes. The effect of fungicides on mycelial growth of Phytophthora sp. and on tomato wilt was evaluated in vitro and in vivo. Two tests were done in Petri plates, and one on seedlings, in completely randomized design as a 4x3 factorial, with 5 replications. In vitro tests were done in growth chamber, at 25 degrees C. The experimental unit consisted of a 5-mm diameter fungal mycelial plug placed 30 mm away from a filter paper disk, of similar size, soaked in fungicide, over cornmeal agar. The first test evaluated four commercial products registered for the control of potato blight: chlorothalonil+metalaxyl (Folio Gold (R) 742.5 WP); propamocarb chloridrate (Infinito (R) 687.5 CS), metalaxyl-m+mancozeb (Ridomil Gold (R) 68 WP), cymoxanil + manconzeb (Curzate (R) MZ 72 WG), at the recommended doses. The other assays evaluated three doses of Infinito (0.125%, 0.150% or 0.175%) and Ridomil. In vivo test was done in the greenhouse, and the experimental unit consisted of one pot, containing one tomato seedling, cultivar Alambra F1. Fungicide was drenched on the seedling soil one day prior to inoculation with 50,000 zoospores per pot. Data of mycelia growth inhibition by fungicide were submitted to analysis of variance and the averages compared by the Tukey test at 5% significance; efficacy was determined as a function of Ridomil (R), the standard fungicide. In the first test, regardless of isolate, Infinito (R) presented performance similar to Ridomil (R) with efficacy of 98.5%, while Folio Gold (R) presented efficacy of 57.3% and Curzate (R) had no fungicide effect. Growth of isolate PP3 was smaller in all fungicides. In the second in vitro test, all three doses of Infinito (R) had efficacy above 82%. The best control was observed on isolates PP3 and PP4. In the third test, in vivo, no significant differences were observed in root matter among the standard fungicide and the doses of Infinito (R); however, efficacy of Infinito (R) at 0.175% was 14% greater than that obtained with Ridomil (R). It can be concluded that Infinito (R) is one more option for the control of tomato wilt.
Keywords: Fungicides; Solanum lycopersicum; Phytophthora sp.